Phase transitions in the Blume-Emery-Griffiths-Vannimenus model on the Cayley Tree - Ganikhodjaev, Nasir (2012)
This is a study on the phase diagram of the Blume-Emery-Griths model on a Cayley tree with competing nearest-neighbour couplings and next-nearest-neighbour couplings and show that a detailed study of its properties can be carried out with essentially exact results, using rather simple numerical methods.